The role of the educational club in contemporary pedagogical reality - Aleksandrovna, Ignatyeva Galina; Nikolaevich, Panfilov Aleksey; Petrovna, Druzyanova Varvara; Ivanovna, Kondakova Nadezhda; Valery Borisovich, Pervozvanski (Opción, 2019)
The aim of the study is to investigate role of the educational club in contemporary pedagogical reality via in-depth study of the school teacher’s classes and curriculum activities and monitoring of two experimental groups of participants at the primary and ultimate stages in the educational club. As a result, the key aim of the educational club is to form and improve certain skills and abilities.As a conclusion, the educational club as a variety of advanced teacher training system within methodical activity of comprehensive schools demonstrated its multisided productivity, including positive influence on the level of teachers’ creative abilities